Nackt unter Wölfen - Beyer, Frank (Germany : DEFA, 1963)
As rumors reach them that the Allied armies are advancing on their concentration camp at Buchenwald, Polish prosoners renew their feeble hope for survival and freedom. When a group of prisoners is transferred from Auschwitz, a four-year-old child is smuggled into the camp in a valise. Born at Auschwitz, he is Jewish and will be killed if discovred. A group of prisoners decide to protect the child, from the searching Germans, and although the kapos cannot smuggle the boy out of Buchenwald, they manage to hide him---moving from one place to another within the camp as the Nazis comb it. Threats and torture by SS men fail to turn up the boy who becomes a symbol of the struggle between captives and captors.
Duration: 01:58:00
Keywords: Fiction films